2023
DOI: 10.3389/fimmu.2023.1214912
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas– induced IRF3 and MAVS knockouts in a salmonid cell line disrupt PRR signaling and affect viral replication

Yorick A. van der Wal,
Henriette Nordli,
Allan Akandwanaho
et al.

Abstract: BackgroundInterferon (IFN) responses are critical in the resolution of viral infections and are actively targeted by many viruses. They also play a role in inducing protective responses after vaccination and have been successfully tested as vaccine adjuvants. IFN responses are well conserved and function very similar in teleosts and mammals. Like in mammals, IFN responses in piscine cells are initiated by intracellular detection of the viral infection by different pattern recognition receptors. Upon the recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Farmed and wild teleost fish are infected with many RNA viruses where (+) RNA and dsRNA virus infections cause high losses, particularly in farmed salmon ( 14 17 ). Hence, understanding MAVS’ contribution to innate responses to SAV-3 (+RNA virus) and infectious pancreatic necrosis (IPN) virus (dsRNA) will shed light on crucial innate and adaptive defense mechanisms of salmonid teleost, and a recent study has shown that MAVS-knock out in vitro impairs PRR-signaling in fish cells ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Farmed and wild teleost fish are infected with many RNA viruses where (+) RNA and dsRNA virus infections cause high losses, particularly in farmed salmon ( 14 17 ). Hence, understanding MAVS’ contribution to innate responses to SAV-3 (+RNA virus) and infectious pancreatic necrosis (IPN) virus (dsRNA) will shed light on crucial innate and adaptive defense mechanisms of salmonid teleost, and a recent study has shown that MAVS-knock out in vitro impairs PRR-signaling in fish cells ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This cell line has proven to be useful to better understand the host-pathogen interaction between salmon and the infectious salmon anemia virus (ISAv) [25]. In our study, this cell line also has proven to be an excellent model for performing genome editing based on the CRISPR-Cas9 system, showing high levels of efficiency for a salmon cell line and relatively high KO efficiency compared to other fish cell lines (23-76%) [26], or in vivo induced mutations in embryos of S. salar by the CRISPR-Cas9 system (13-50%) [27,28], providing a useful initial step for research in salmonid species to better understand the specific role of gene regulation on infectious diseases and immune responses.…”
Section: Fish Cell Lines and Crispr-cas9 System As Genome-editing Too...mentioning
confidence: 89%
“…A study on the CHSE-214 cell line used the CRISPR-Cas9 system to evaluate the effect of a knock-out of the genes mavs, irf3, irf7-1, and irf3/7-1 (double KO) on PRR signaling [26]. The evaluation of Interferons (IFNs) and IFN-stimulated genes by qPCR after Poly I:C stimulation showed an inhibition of the expression in the mavs and irf3 edited groups, showing the advantages of using CRISPR edited cell lines in fish for understanding the immune response and the host-pathogen interaction.…”
Section: Fish Cell Lines and Crispr-cas9 System As Genome-editing Too...mentioning
confidence: 99%